Indonesia's Higher Education System : How Responsive is it to the Labor Market? - World Bank (Washington, DC, 2014)
Indonesia is at a development crossroads. It successfully weathered the 2008 international financial crisis, and it has shown resilience in the current turbulent times. Its economy is now one of the largest 20 economies in the world and it has ambitious plans to achieve high-income status and join the G-7 by 2030. Yet the challenges it faces are daunting. As highlighted in the recent Indonesia Economic Quarterly report by the World Bank, the status quo may not be enough to maintain current growth rates in light of domestic and policy pressures. And even maintaining the current rates of growth will not bring the country to high income status by the target year. This paper is organized as follows. Section two presents a framework to look at incentives and argues that without the right system in place, the tendency of the education sector will not necessarily be to align its supply with the demands of the labor market. The section discusses some of key features of the system in Indonesia. Section three looks at the performance of higher education graduates in the labor market, their labor force participation, unemployment rates, the types of jobs they obtain and trends in the returns to higher education. Section four takes patterns in employment and returns to education, as well as employer surveys, to find signs of misalignment between supply and demand in the types of degrees of graduates, the sectors where they are employed and the skills they bring with them. Finally, section 5 concludes with some suggested policy directions and future research.